POLA PERESEPAN OBAT GASTRITIS DI PUSKESMAS PANGALE KABUPATEN MAMUJU TENGAH PERIODE JANUARI – AGUSTUS TAHUN 2020 - Imran Firman; Cici Dewi Andriani (KOLONI, 2022)
Gastritis is inflammation of the stomach due to increased acid secretion and as a disease mostly found in the society. Based on the results of observations og gastritis at the Pangale Public Health Center, there was is quite high at Central Mamuju Regency. This study aimed to determine prescription patterns of gastritis drugs at Pangale Public Health Centre of Central Mamuju Regency in period January-August 2020. This research was conducted using a descriptive method by collecting data retrospectively on the recipes of gastritis patients. In this study, 103 samples were includedinclusion criteria. The results showed that most gastritis sufferers were women with a percentage of 56.31%, with an age group of 46-55 years (30.10%) and 32.04% SD level education and 42.72% type of occupation. Based on the characteristics, the most frequently drug classes were antacids as much as 79.61% and Antasida Doen were the most widely used drug items (79.61%). The most widely used combination of drugs was antacids + h2-blockers of 47.46%. 100% generic prescription. The accompanying drug, namely vitamin B complex of 46.60% and the dosage form was tablets (98.06%). All drugs used indicate gastritis. Some of the doses were not suitable and the duration of administration was mostly appropriate. The length of giving drugs showed omeprazole for the longest period of 10 days. The rules for using all drugs are given before meals and the most widely used gastritis drugs is Antasida doen with a percenrage of 79.62%. Keywords: Gastritis, drug prescription